Profiling analysis of protein tyrosine phosphatases during neuronal differentiation. (26th January 2016) - Kim, Sun Young; Oh, Mihee; Lee, Kyu-Suk; Kim, Won-Kon; Oh, Kyoung-Jin; Lee, Sang Chul; Bae, Kwang-Hee; Han, Baek-Soo
Highlights: We checked the expression profiling of PTPs during neuronal differentiation. The mRNA and protein of DUSP23 were increased and the knockdown of DUSP23 reduced neuronal differentiation. The phosphorylation status of ERK, JNK, and p38, respectively, was affected by manipulation of the DUSP23 gene. Abstract: During neuronal differentiation, it is generally accepted that many kinases and phosphatases fulfill different roles. In this study, phospho-tyrosine phosphatases were focused on and their expression profiling was evaluated during neuronal differentiation of mouse J1 embryonic stem cells. Among 83 phospho-tyrosine phosphatases, expressions of 21 PTPs were increased but mRNA expressions of 10 PTPs decreased depending on the differentiation. We checked the protein expression patterns for the cases where PTPs mRNA expressions changed. Some of them showed consistent results with the mRNA expressions. In particular, it was found that dual-specific phosphatase23 (DUSP23) affected neuronal differentiation. The knock-down of DUSP23 decreased neuronal differentiation in terms of neuronal outgrowth and the expression of neuronal marker proteins and mRNAs. Taken together, the obtained results show that many PTPs play specific roles during neuronal differentiation and manipulating their activities by activators or inhibitors could adjust neuronal differentiation.